The Diachronic perspective of semantic structures - an interface between the structural and the cognitive approach - Raffaelli, Ida (2005)
U radu se opisuje dijakronijska dinamika semantičkih struktura spregom strukturalističkoga i kognitivnog pristupa jeziku.
ENG